Understanding the new Philippine competition act - Erlinda M. Medalla (Philippine Institute for Development Studies (PIDS), 2017)
After numerous attempts over more than a decade, the Philippine government finally enacted a comprehensive competition law, the Philippine Competition Act (Republic Act 10667) in July 2015. Before this breakthrough legislation, competition policy and law was scattered in about 30 different laws (for instance, the Philippine Constitution, Revised Penal Code, Consumer and Price Acts, and sector-specific regulations), with outdated provisions and hardly any jurisprudence. The passing of the law is only the first step. Much needs to be done to establish a truly working competition policy, including capacity building, and dissemination, information, and education for the law. This paper attempts to contribute in this regard by examining the provisions of the new law and providing an overview of what it covers, what it can do, and what could be the possible implications for related policies. As such, this paper has three major sections. The first provides an overview of the rationale and objectives of competition law. The second discusses the major provisions of the new law, including some comments to highlight important provisions. The third section provides an overall assessment of the act and additional comments and observations. The section also briefly looks at the case of PLDT/Globe acquisition of the San Miguel Corporation's telecommunications assets.
Keywords: 330; competition policy and law; Philippine Competition Act; anti-competitive behavior